👤

Sa se rationalizeze:
[tex] \frac{1}{ \sqrt[4]{7}- \sqrt[4]{3} } [/tex]
[tex] \frac{1}{ \sqrt[6]{2}-1 } =[/tex]
[tex] \frac{1}{ \sqrt[5]{3}+\sqrt[5]{2} } [/tex]


Răspuns :

ex.1 =  (⁴√7  + ⁴√3)  / ( ⁴√7 -⁴ √3) ·(⁴√7 + ⁴√3)  = ( ⁴√7 + ⁴√3)  / ( √7 - √3) 
                                               ↓ 
                                              ⁴√7²  - ⁴√3² = √7 - √3
= (⁴ √7  +  ⁴ √3 ) ·(√7 + √3)  /  ( √7 -√3) · (√7 + √3) 
                                                        ↓
                                                  √7²   - √3² = 7 -3 = 4 
= (⁴√7 + ⁴√3) · (√7 + √3)  / 4 



  ex2.=  (⁶ √2² +  ⁶√2 + 1)  / ( ⁶√2 -1) · (⁶√2² + ⁶√2 +1)  
                                                      = a³ - b³ 
                                                   = ⁶√2³  - 1³ = √2  - 1  
= (⁶√4 + ⁶√2 + 1 ) / (√2 -1)  = 
 = ( ⁶√4 +   ⁶√2 +1 )· (√2 +1)  / ( √2 -1) · (√2 +1 )  =  
                                                           ↓
                                              √2²   - 1 = 2 -1 =1 
= (⁶√4 + ⁶√2 +1) · (√2 +1)


a⁵ + b⁵ = ( a +b) ( a⁴ -a³b+a²b² -ab³ + b⁴ )

   ex.3 = (⁵√3⁴ - ⁵√3³ · ⁵√2 + ⁵√3² · ⁵√2² - ⁵√3 · ⁵√2³ + ⁵√2⁴ )  / ( 3 +2 ) 
         = ( ⁵√81  - ⁵√54   + ⁵√36 - ⁵√24 + ⁵√16 ) / 5